Speech Act in Talk Show: Locutionary, Illocutionary and Perlocutionary Acts in the Oprah Winfrey Show - Retno Ningsih, Tri Wahyu; Rahayu, Rusiana; Purwaningsih, Endang (Ikatan Sarjana Komunikasi Indonesia, 2023)
The objective of this study is to analyze the kinds of speech acts performed by Oprah Winfrey. The theory in this research is the speech act theory (locutionary, illocutionary, and perlocutionary acts) from Searle. The study used a descriptive qualitative approach. The data were taken from The Oprah Winfrey Show in the episode with special guest stars Celine Dion, Milagros, and Dink Donald. The results of the research obtained are the most dominant data of perlocutionary act is to get the hearers to do something which occurred in 14 times which represent 28.26%. The highest category of illocutionary acts is directives that occur in 23 times which represent 46.3%. The most dominant illocutionary act of directives is the act of asking that occur in 9 times which represent 18.4%. It happened because Oprah Winfrey as the host often asked the guest stars as the hearers to answer the questions from her as the speaker. It reflects to the purpose of talk show which is to find out and get information from the guest stars, thus the audiences in the studio and the viewers at home could get the information. The hearers were not only the guest stars, but the audiences and the viewers at home also involved. Directives are the most illocutionary acts performed by Oprah Winfrey because she often asked the guest stars to answer the questions from her. It reflects to the purpose of talk show which is to get information. The most dominant data of perlocutionary acts are to get the hearers to do something. It made the talk show became interactive and communicative.